Selective Adsorption and Purification of the Acteoside in Cistanche tubulosa by Molecularly Imprinted Polymers - Zhao, Xiaobin; Pei, Wenjing; Guo, Ruili; Li, Xueqin (Frontiers in Chemistry, 2020)
Molecularly imprinted polymers (MIPs) were designed and synthetized to adsorb selectively the acteoside (ACT) in Cistanche tubulosa. The effects of different functional monomers, crosslinkers and solvents of MIPs were investigated. MIPs were studied in terms of static adsorption experiments, dynamic adsorption experiments, selectivity experiments. The optimal functional monomer, crosslinking agent and solvent are 4-vinylpyridine, ethylene glycol dimethylacrylate, and the mixed solvent (acetonitrile and N, N-dimethylformamide ,1:1.5, v/v), respectively. Under the optimal conditions, the synthesized MIP1 has a high adsorption performance for ACT. The adsorption capacity of MIP1 to ACT reached to 112.60 mg/g, and the separation factor of ACT/echinacoside was 4.68. Because the molecularly imprinted cavities of MIP1 resulted from template molecules of ACT, it enables MIP1 to recognize selectively ACT. Moreover, the N-H groups on MIP1 can form hydrogen bonds with the hydroxyl groups on the ACT, this improves the separation factor of MIP1. The dynamic adsorption of ACT accorded with the quasi-second-order kinetics, it indicated that the adsorption process of MIP1 is the process of chemical adsorption to ACT. MIPs can be applied as a potential adsorption material to purify the active ingredients of herbal.